Haemoglobin, haematocrit and red blood cell indices in elite cyclists. Are the control values for blood testing valid? - Schumacher, Y. O.; Grathwohl, D.; Barturen, J. M.; Wollenweber, M.; Heinrich, L.; Schmid, A.; Huber, G.; Keul, J. (International Journal of Sports Medicine, 2000)
BACKGROUND: In international cycling and cross-country skiing competitions, blood tests are used to unmask the performance enhancing misuse of erythropoietin. Haematocrit (cycling) and haemoglobin (cross-country skiing) limits have been set by international sporting federations (haematocrit 50%, haemoglobin 18.5 g/dl). Athletes tested above these cut-off values are declared unfit for competition. To investigate the validity of these regulations, we studied haemoglobin, haematocrit and red blood cell indices of elite cyclists before erythropoietin became commercially available. MATERIAL AND METHODS: We investigated 523 blood samples of 92 male elite cyclists (age 16-31 years) from 1978 to 1987. Haematocrit, haemoglobin and red blood cell count were analysed automatically, erythrocyte indices were calculated. RESULTS: Haemoglobin (-0.3 +/- 1 g/dl), haematocrit (-1.2 +/- 2.8%) and red blood cell count (-0.2 +/- 0.4 x 10(6)/mm3) decreased significantly (p < 0.05) with increasing training workload. The erythrocyte indices showed no significant change. Fifty-four blood samples (10.3%) showed a haematocrit above 50%, one sample presented a haemoglobin mass higher than 18.5 g/dl. During periods of increased workload, less athletes tested above the haematocrit limit. CONCLUSION: The current haematocrit limit used in blood tests might lead to a high number of false positive tests.